Pengaruh Penumbuhan Bioflok pada Budidaya Udang Vaname Pola Intensif di Tambak [The Effect Of Biofloc Growing On Vannamei Shrimp Culture At Intensive System Pond] - Gunarto Gunarto; Nur Ansari Rangka (Jurnal Ilmiah Perikanan dan Kelautan, 2012)
Abstract The objective of the research are to monitor of floc and same parameters production of Litopenaeus vannamei cultured in concrete pond. Two unit of concrete ponds consist of one pond real conccrete pond cemented in the dike and pond bottom, it size 3250 m2 (A pond) was stocked with vanname post larvae day 10 at density 170 ind./m2 (561.200 ind.). The other one pond only cemented in the dike, whereas the pond bottom still of sandy soil, its size 3915 m2 ( B pond) was stocked with vanname post larvae day 10 at the density 148 ind./m2 (579.600 ind.). These ponds were monitored started from pond preparation stages untill shrimp harvested. In A pond , after two months shrimp cultured, at every two days the pond waters was added 15 kg of molasses in order to enhance the CN ratio, so that the floc can growth easily. B pond was control pond without molasses addition. Both of these ponds were added with varies of probiotic shifted daily. Monitored on srimp feed given to the shrimp showed that after post larvae stocked in pond, the feeed given to the post larvae at the dosage 3 kg crumble feed/100.000 ind. post larvae. The quantity of shrimp feed increases to 6 kg/100.000 ind post larvae at the day of culture 20 - 25. Then after that period the quantity of feed given to the shrimp follow the standard feeding program and depend on the feeding monitoring in trays (anco). Shrimp survival rate, production and feed convertion were monitored after shrimp harvested. Water quality, total bacteria and total Vibrio sp were monitored beweekly. TSS, VSS and floc volume were monitored after floc develop in pond waters. Result of the research showed that floc develop in A pond at the day 75, while in B pond after the day 90. Ammonium concentration in pond waters was decreases coinsides with the developing floc in A and B pond. However, nitrite decreased only in B pond and Vibrio sp population was stagnant. Shrimp harvested in both ponds at two times, first at the day 110 and secondly at the day 140. Shrimp production attained 11.123,5 kg (34.226,15 kg/Ha), survival rate 88,55%, feed convertion 1 : 1,82 and shrimp size 41,7 – 52 ekor/kg in pond A. In B pond shrimp production is15030 kg (38.390,8 kg/Ha), survival 99,6%, feed convertion 1 : 1,66 and shrimp size 36,5 – 46,5 ind./kg. Based on this research indicated that in A pond more fasted floc develop compared than that of B pond. However, shrimp production was lower, feed convertion was higher in A pond compared than that of B pond. Total yields in plots A (flock) of 11123.5 kg (34226.15 kg / ha), with 88.55% survival rate, feed conversion 1: 1.82. The average size of 46 shrimp tails / kg. In plot B the production of 15 030 kg (38390.8 kg / ha), 99.6% survival rate, feed conversion of 1.66, the size of the shrimp tails 41.5 / kg. Based on these results suggest that although the plot A flock is formed faster than in plot B, but lower shrimp production and feed conversion value is higher than that obtained in plot B. The analysis focused on the cultivation of farms with the highest production of plot B is converted in a total of 36 308 kg ha (an average of 34226.15 kg / ha - 38390.8 kg / ha) with a value of Rp. 805.465.160/season. Vaname shrimp farming can be done two times a year. Reveniu calculation cost ratio (R / C ratio) value of 2.02 indicates the feasibility of (2.02> 1) in a season of business, while for the Benefit cost ratio (B / C ratio) of 1.02 (1.02> 1) is worthy of sustained effort.